TINJAUAN SEJARAH TERHADAP MUSIK TRADISI SULING BAMBU DALAM MASYARAKAT SIULAK MUKAI (1998-2021) - Uftiyah Ganozhy Usman; Rusdi (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
This study aims to describe the historical changes and existence of Bamboo Flute Traditional Music in Siulak Mukai, Kerinci Regency and to analyze the survival process of Bamboo Flute Traditional Music in the Siulak Mukai community in the period 1998 to 2021. This study follows the official procedure of historical research which consists of four stages: heuristics , criticism, interpretation, and historiography (writing). The result of this research is that in 1998-2001, traditional music of Bamboo Flute in the Siulak Mukai community is an art that has its own uniqueness and is popular among the public. Bamboo Flute music which was originally played in his spare time when he was bored while repelling birds in the cultivated fields and also while resting on the plantations. Then in 2001-2014, this traditional music of Bamboo Flute underwent adaptation to globalization. Along with the development of the way of life of the local community, there is also a development for the Bamboo Flute, where at this time there is a development in the form and presentation of the Bamboo Flute, which was originally worked at a rather slow tempo, has developed with two variants from both sides of the presentation. modern. And in the span of 2001-2014, the development of Bamboo Flute traditional music in the Siulak Mukai community did not stop with the progress of life and technology, but the Bamboo Flute traditional music experienced developments and changes in accordance with the ongoing demands of life. Furthermore, in the 2015-2021 range, the changes that occurred were the mixing or collaboration between traditional music of Bamboo Flute and modern music with the addition of musical instruments such as piano, guitar, drums, and so on. in terms of performances or in terms of songs sung. From the changes that have occurred, the community is very supportive and considers that this change is a good step to preserve these traditional arts.